MARKETING STRATEGY FOR SOFT BONED MILKFISH MSME PRODUCTS IN SEMARANG CITY DURING THE COVID-19 PANDEMIC - Tutianvia, Aldise Kresna Dewi; Suherman, Agus; Mudzakir, Abdul Kohar (JFMR (Journal of Fisheries and Marine Research), 2021)
The Covid-19 pandemic has had a significant impact on various sectors, including Micro, Small and Medium Enterprises (MSMEs). One of the MSMEs affected is the soft boned milkfish MSME. This study aims to analyze the impact of the Covid-19 pandemic and determine the marketing strategy for soft boned milkfish products in Semarang. The method used in this research is a survey method. Primary data were obtained from 75 SMEs of soft boned milkfish in Semarang City, secondary data was obtained from related books and journals. The data analysis used is descriptive analysis and SWOT analysis. Descriptive analysis is used to determine the impact of the Covid-19 pandemic on the marketing of soft boned milkfish MSME products, SWOT analysis is used to develop alternative strategies for soft boned milkfish MSMEs during the COVID-19 pandemic. The results of the analysis show that the Covid-19 pandemic has an effect on the decline in the number of sales of production products, the number of customers and the number of requests by >50%. Alternative marketing strategies for soft boned milkfish MSME products in Semarang during the Covid-19 pandemic are: a) Branding (trademark) on each product packaging; b) Create attractive packaging designs; c) Registration of Business Permit, Submission for Issuance of SKP (Certificate of Eligibility Processing), Registration of SNI and legality; d) Cooperating with raw material suppliers to meet customer demands; e) Changing the atmosphere of sales outlets/stores by implementing health protocols.